Genomic analysis of adult B-ALL identifies potential markers of shorter survival. (May 2017) - Patel, Shiven; Mason, Clinton C.; Glenn, Martha J.; Paxton, Christian N.; South, Sara T.; Cessna, Melissa H.; Asch, Julie; Cobain, Erin F.; Bixby, Dale L.; Smith, Lauren B.; Reshmi, Shalini; Gastier-Foster, Julie M.; et al.
Highlights: B-cell developmental genes are recurrently deleted in adult B-ALL. Most common copy number losses were in the genes CDKN2A, IKZF1, and PAX5 . EBF1 deletion was associated with significantly worse relapse free survival. Patients with CDK2NA and IKZF1 deletion showed a trend toward shorter survival. Abstract: B lymphoblastic leukemia (B-ALL) in adults has a higher risk of relapse and lower long-term survival than pediatric B-ALL, but data regarding genetic prognostic biomarkers are much more limited for adult patients. We identified 70 adult B-ALL patients from three institutions and performed genome-wide analysis via single nucleotide polymorphism (SNP) arrays on DNA isolated from their initial diagnostic sample and, when available, relapse bone marrow specimens to identify recurring copy number alterations (CNA). As B-cell developmental genes play a crucial role in this leukemia, we assessed such for recurrent deletions in diagnostic and relapse samples. We confirmed previous findings that the most prevalent deletions of these genes occur in CDKN2A, IKZF1, and PAX5, with several others at lower frequencies. Of the 16 samples having paired diagnostic and relapse samples, 5 showed new deletions in these recurrent B-cell related genes and 8 showed abolishment. Deletion of EBF1 heralded a significant negative prognostic impact on relapse free survival in univariate and multivariate analyses. The combination of both a CDKN2A/B deletion and an IKZF1 alteration (26% of cases) also showed a trend toward predicting worse overall survival compared to having only one or neither of these deletions. These findings add to the understanding of genomic influences on this comparably understudied disease cohort that upon further validation may help identify patients who would benefit from upfront treatment intensification.